Quality comparison of tomato leather made from flour agar gracilaria sp resulted from coconut water extraction and flour comercial agar - Rista Anggriani; Noor Harini; Shandra Berliana (Universitas Darussalam Gontor, 2020)
Tomatoesas climacteric fruit have a high water content of around 94% which causes spoilage, whereas tomatoes have vitamin C of about 5.78 mg/50 gwhich is beneficial for health. Thus the processing is needed to extend its shelf life. Fruit leatheris processed from fruit flesh in the form of dry thin sheets that are easy to roll. A plastic texture is a requirement for fruit leather, so the additionof gelling agents is needed. Previous research has succeeded in extracting agar from Gracilaria sp seaweed using coconut water that meets FAO standards. Therefore the aim of this research is to apply the agar results from coconut water extraction to the fruit leatherand to compare the quality of the fruit leatherusing commercial agar. The experimental design used was a simple randomized block design with 4 treatments, consisted of fruit leathertomatoes using agar extract from coconut water and commercial agar at two concentrations (0.6 and 0.9%). The results obtained between the quality of the fruit leathertomatoes and the agar results from coconut water extraction with commercial agar showed almost the same characteristicin all parameters both in chemical, physical and sensory characteristics, although statistically there were differences in notations on moisture content, TPT, thickness and tensile strength. This indicates that the agar from coconut water extraction can act as a gelling agentby producing fruit leatherthat its quality is almost the same as commercial agar.